PARTICIPAÇÃO ESCOLAR: UMA ANÁLISE A PARTIR DA HISTÓRIA DE VIDA DOS PARTICIPANTES - Sanches, Silvana Lopes (2008)
This study is essentially a reflection about participation in a school of the São Paulo state network of schools, based on the life history of the persons that work there, with the purpose of understanding what keeps these persons motivated to sustained participation. It is a qualitative research that reports the background of the author and of two other persons of the school community using the life history method. This study was conducted in three steps. In the first, and by means of the life history interview method, the author got to know the subjects involved in school participation. In the second, current literature on the concepts of participation and volunteering was examined. The third step was a reflective analysis of the life history of the subjects in the light of multicultarility, participation, and volunteering. This analysis showed that the persons involved underwent a significant change evolving from naïve participation to critical participation.(AU)